KARAKTERISTIK DINAMISITAS HUKUM MUAMALAH TENTANG RAHN DALAM TEORI DAN PRAKTIK (Pertarungan Antara Formalitas Versus Substansialitas Hukum Muamalah) - Uddin, Jamil; Afriadi, Wawan (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
Rahn, as a topic discussion, in Muamalah studies is indivisible from some theories developed by Islamic scholars to formulate various substantive practices. This study deployed literature-review as a research method in purpose to discuss some secondary and primary data such as Islamic-law from the Quran, Al-Hadiths and affirmative-law in Indonesia with Fiqh books as a writing guidance. The results found that there were some similarities and differences regarding Rahn based on two scholars; Hanafi’s and Syafi’s perspectives. In establishing a law (law-istinbath) by Abu Hanifah was utilizing his own Fiqh to be more substantial to discuss the Rahn or Law Istinbath (law establishment) method. What had been done by this mazhab was basically from the Quran, Al-Hadits (As-sunnah), Aqwal al-Shahabah (The opinion of the prophet’s companions), Ijma’, Qiyas, Istihsan, and Urf (Custom). Meanwhile, Al-Imam Syafi’i conceptualized the law istimbath (law-establishment) by the reference in his I’rab Ar-risalah; the Quran, As-sunnah, Ijma’, Qiya, and Istidlal (Istishab). The similarities and differences according to Hanafiyah-scholars that the mazhab divided into two categories in which as absolute approval and absolute refusal. To Syafi’iyah-scholars that the murtahîn were forbidden to utilize the marhun yet they only had right to detain it. The Marhun can only be used by Râhin as the owner. However, in term of Râhin gave permission, the Marhun could utilize it.